Boiled, sprouted, and raw cowpea‐incorporated diets modulate high‐fat diet‐induced hypercholesterolemia in rats. Issue 6 (13th August 2018) - Liyanage, Ruvini; Perera, Oshini; Lakmini, Gusthingna W. A. S.; Weththasinghe, Pabodha; Visvanathan, Rizliya; Jayathilake, Chathuni; Jayawardana, Barana C.; Vidanarachchi, Janak; Sivakanesan, Ramiah
Abstract: This study was carried out to investigate the effect of processed (boiled and sprouted) cowpea‐incorporated experimental diets on serum cholesterol and serum antioxidant capacity in high‐fat diet (HFD)‐fed Wistar rats. Seven weeks old male Wistar rats were fed 20% fat as a control (CD), for comparison with 20% fat‐enriched diets containing 20% whole raw cowpea diets (Bombay Raw Diet; BRD and MI35 Raw Diet; MRD), boiled cowpea diets (Bombay Boiled Diet; BBD and MI35 Boiled Diet; MBD) and sprouted cowpea diet (Bombay Sprouted Diet; BSD) for 6 weeks. The increase in serum total cholesterol as a result of high‐fat diet was significantly countered by boiled and raw cowpea‐incorporated diet‐fed rats. Increased serum non‐HDL‐C level caused by HFD was significantly ( p < 0.05) countered by raw, boiled, and sprouted cowpeas, while HDL–C was increased by raw MI and boiled Bombay incorporated diets. Boiling has improved the hypocholesterolemic ability of Bombay cowpea and BBD has significantly ( p < 0.05) modulated serum HDL‐C level and liver weight in rats. These findings were supported significantly high soluble fiber content in processed cowpea powder than that in raw cowpea powder. The decrease in serum antioxidant activity as a result of HFD was significantly countered by BRD. Processing has reduced the antioxidant activity in cowpeas and serum antioxidant activity in rats. Cecal lactobacilli population was significantly high in all cowpea diet‐fed groups compared to control. Modulated serum cholesterol level in cowpea diet‐fed rats was accompanied by dietary fiber composition, antioxidant activity in cowpeas and fecal weight, cecal weight and cecal lactobacilli population in rats compared to control. Both processed and raw cowpea‐incorporated diets have modulated HFD‐induced hypercholesterolemia by modulating serum antioxidative capacity, cholesterol metabolism, and cecal fermentation. Abstract : Boiled, sprouted and raw cowpea incorporated diets have modulated HFD induced hypercholesterolaemia by modulating cholesterol metabolism and cecal fermentation.The increase in total cholestreol and non HDL‐C level as a result of HFD was significatly encountered by boiled, raw cowpea diets and boiled, sprouted cowpea incorporated diets, respectvely. Lower serum cholesterol level in cowpea fed rats was supported by higher serum antioxidant activity and higher cecal lactobacilli population compared to control diet.